EFEKTIVITAS PELAKSANAAN TUGAS DAN FUNGSI PEMERINTAH KECAMATAN - Suaiba Suaiba (Fakultas Hukum Universitas Islam Malang, 2020)
ABSTRACT The task of the Indonesian government is very important in realizing the objectives of the task force is a very broad task, so that regulations are needed that can direct the administration of government to be more in line with the expectations and needs of the community. The task of the Indonesian government is very important in realizing the goals of the country. This thesis problem formulation is about How does the effectiveness of the duties and functions of government officials in the District, and factors that play a role in providing services to the community in the District. This type of research is empirical juridical and uses a sociological approach. The results of this study indicate that the implementation of the duties and functions of the Sub-district government officials in providing services to the community are considered not yet fully effective, on the other hand, the district head in carrying out his duties in accordance with the Local Government Law No. 23 of 2014 which states that the district head is authorized to coordinate the implementation of government activities carried out by the Government carried out by the Regional Apparatus in the District. Key words: Effectiveness, Duties and Functions, District Government. ABSTRAK Tugas pemerintahan Indonesia sangatlah penting dalam mewujudkan tujuan negara. Tugas tersebut merupakan tugas yang sangat luas, sehingga diperlukan peraturan yang dapat mengarahkan penyelenggaraan pemerintahan menjadi lebih sesuai dengan harapan dan kebutuhan masyarakat. Rumusan masalah skripsi ini adalah mengenai Bagaimana efektifitas tugas dan fungsi aparat pemerintah di Kecamatan, dan Faktor-faktor apa saja yang berperan dalam pemberian pelayanan kepada masyarakat di Kecamatan. Jenis penelitian ini yakni yuridis empiris dan menggunakan pendekatan sosiologi. Hasil penelitian ini menunjukkan bahwa pelaksanaan tugas dan fungsi aparat pemerintahan Kecamatan dalam pemberian pelayanan terhadap masyarakat dianggap belum sepenuhnya efektif, disisi lain, Kepala Camat dalam menjalankan tugasnya sesuai menurut Undang-Undang Pemerintahan Daerah Nomor 23 Tahun 2014 yang menyatakan bahwa camat berwenang untuk mengoordinasikan penyelenggaraan kegiatan pemerintahanyang dilakukan oleh Pemerintahan yang dilakukan oleh Perangkat Daerah di Kecamatan. Kata kunci: Efektivitas, Tugas dan Fungsi, Pemerintah Kecamatan.